2012
DOI: 10.1127/0003-5548/2012/0179
|View full text |Cite
|
Sign up to set email alerts
|

Body mass reconstruction on the basis of selected skeletal traits

Abstract: Males Females t-value p N-males N-females S.D. males S.D. females F p Femoral head 48.4808 43.81-5.277 0.000 26 20 2.12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Pelvic shape differentiation in males cannot be explained as a consequence of differences in body stature, as we found that base of the sacrum area and overall pelvic size computed as centroid size were similar in the medieval and contemporary samples. Body stature was similar in these two groups: the average body height was 175 cm for males from Cedynia (Myszka, 2017), 178.3 cm for modern Polish men (Kołodziej et al, 2015). Moreover, the observed differences are not a result of pelvic allometry (the correlation between pelvic shape and size), as demonstrated by non-significant regression analysis ( p > 0.05).…”
Section: Discussionmentioning
confidence: 89%
“…Pelvic shape differentiation in males cannot be explained as a consequence of differences in body stature, as we found that base of the sacrum area and overall pelvic size computed as centroid size were similar in the medieval and contemporary samples. Body stature was similar in these two groups: the average body height was 175 cm for males from Cedynia (Myszka, 2017), 178.3 cm for modern Polish men (Kołodziej et al, 2015). Moreover, the observed differences are not a result of pelvic allometry (the correlation between pelvic shape and size), as demonstrated by non-significant regression analysis ( p > 0.05).…”
Section: Discussionmentioning
confidence: 89%
“…a number of investigators use methods employing formulae based on body height to estimate body mass (Jungers, stern 1983;ruff, Walker 1993;Wolpoff 1983), while others use standard methods based on morphological parameters such as femoral head or cross-sections (Jungers 1988;Mchenry 1988;. the results of such studies are often contradictory, because they use only partial information, preferring to obtain a high number of estimates rather than assure their comparability (Myszka et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…2005), the most important information can be yielded by skeletal material only. therefore, numerous authors have analysed relevant skeletal material to describe basic evolutionary trends over the upper palaeolithic/ neolithic transition and the origin of agriculture (e.g., Formicolla 1983;Formicolla, Franceschi 1996;Formicolla, giannecchini 1999;Frayer 1980;1981;1984;Frayer, Wolpoff 1985;holliday 1997;Jacobs 1985a;pinhasi 2004;pinhasi, von cramon-traubadel 2009;2012;ruff 1987;ruff et al 1984;1997;Vančata 1988;2005).…”
Section: Introductionmentioning
confidence: 99%
“…In total, 15 muscle/ligament attachment sites on upper limbs were assessed on macerated bones (scapulae, humeri, and ulnae, Table 1). We chose these attachment sites because they (a) are easy to assess and distinguish (Weiss, 2003); (b) are often used to reconstruct levels of activity in other research (e.g., Hawkey & Merbs, 1995; Myszka, 2007; Sládek, Hora, et al, 2016; Sládek, Ruff, et al, 2016; Weiss, 2003); (c) are associated with muscles responsible for the upper limb's activities (Bochenek & Reicher, 2010; Stone & Stone, 2011); and (d) show variability in development (Mariotti, Facchini, & Belcastro, 2007). Moreover, the analyzed entheses belong to one of two types, fibrous or fibrocartilaginous, of muscle attachment (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The morphology of bones can change during life via a process of bone modeling in order to better respond to mechanical loading (e.g., Cashmore, 2009; Kivell, 2016). Therefore, variability in bone morphology is often used to reconstruct activity levels and patterns of archeological groups (e.g., Hawkey & Merbs, 1995; Messina & Sìneo, 2010), division of labour according to sex (Eshed, Gopher, Galili, & Hershkovits, 2004), socioeconomic status (Bigoni, Krajíček, Sládek, Velemínský, & Velemínska, 2013; Havelková, Hladík, & Velemínský, 2013), origins of lateralisation (Lazenby, 2002), asymmetry in activity (Fatah, Shirley, Mahfouz, & Auerbach, 2012; Kubicka, Nowaczewska, Balzeau, & Piontek, 2018; Sládek et al, 2016; Sládek, Hora, Farkašová, & Rocek, 2016), somatic structure (Myszka, 2007), and mobility and workload (Larsen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%